(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, the improvement of geographical concepts in elementary school students, the introduction of new theoretical and practical knowledge about the laws of nature and social development into the educational content, the acquisition of knowledge important for social life experiences and various fields of science. training of creative specialists is considered a priority for them, determining the coherence between them, that is, interdisciplinary connections, forming geographical concepts in elementary school classes, studying geographical phenomena and processes, previously mastered in academic subjects issues of acquiring knowledge and skills are described.